COMPARATIVE ANALYSIS OF ADJECTIVES IN ENGLISH AND UZBEK LANGUAGES - Axmedov, Ikboljon (QO‘QON UNIVERSITETI XABARNOMASI, 2024)
This paper explores the similarities and differences in the use and structure of adjectives in English and Uzbek, focusing on linguistic features such as degrees of comparison, syntactic roles, and morphological characteristics. Drawing upon theoretical studies and linguistic data from both languages, this study highlights how cultural and grammatical systems influence adjective usage. The findings reveal that while both languages use adjectives to modify nouns and express qualities, they differ in morphological complexity and usage patterns. Suggestions for integrating these insights into language learning and translation studies are provided.